THE EXPRESSION OF EUPHEMISMS IN THE TRANSLATION OF PUBLICISTIC TEXTS (American Journal of Pedagogical and Educational Research, 2026)
This article analyzes the specific features of expressing euphemisms in the translation of publicistic texts. Euphemisms used in publicistic style are closely related to social, political, and cultural factors, and maintaining semantic accuracy and stylistic appropriateness in the translation process is of great importance. The study examines the semantic and pragmatic aspects of euphemisms, as well as the main strategies used in their translation. Based on examples, methods such as direct translation, adaptation, and explanation are analyzed. As a result, it is substantiated that the proper rendering of euphemisms in the translation of publicistic texts is an important factor in improving translation quality.